YOUNG GENERATION TAX COMPLIANCE AS CANDIDATES POTENTIAL TAXPAYERS - Linawati Linawati; Rezi Eka Putra (Sean Institute, 2023)
Tax compliance is something that is often encountered in tax practices that affects the target of state treasury revenues. The public's perception of tax compliance is of course different and there are many factors that influence it. Students are the nation's successor generation because there are not a few students who have earned income that has met subjective and objective requirements but do not understand taxes so that they finally ignore their tax obligations. This study aims to assess student perceptions related to testing understanding of taxation, a sense of nationalism, trust in the government, tax awareness and tax rates on tax compliance. The method used in this research is descriptive method with a quantitative approach. The population in this study are students of the D4 study program. Pamulang University tax accounting. The stages of the research method start from collecting data through questionnaires. the sampling technique was determined based on purposive sampling, then the data was processed using multiple linear regression analysis. The results of the study show the first hypothesis, namely tax understanding has no effect on tax compliance, and other variants, namely a sense of nationalism, trust in the government, tax awareness and tax rates have an effect on tax compliance.